Institutional environment, technical executive power and agricultural enterprise innovation performance - Limei Cheng (Taylor & Francis Group, 2020)
The interaction between the organization and the institutional environment leads to organizational change or innovation. As the basic industry of China’s national economy, agricultural enterprises are transmitted from the institutional environment to the internals of the enterprise and are transformed into innovative behaviors, which ultimately form performance. Based on the research paradigm of “institution-behavior-performance”, it is of great significance to promote the association between formal and informal institutions, technical executive power and agricultural enterprise innovation performance. This article studied a sample of 164 listed agricultural enterprises from 2009 to 2017 and adopted the negative binomial regression to determine the relationship between institutional environment and innovation performance of these enterprises. The results of the studies show that the more perfect the formal system, the better the innovation performance of agricultural enterprises, while the informal system inhibits the innovation performance of enterprises. The technical executives play a positive intermediary role between formal institutions and innovation performance. However, it does not have a significant intermediary effect between informal institutions and innovation performance.